Descriptions of the first-instar larva of the hypogaeic species Neobidessodes limestoneensis (Watts & Humphreys) and of the third-instar larva of Hydroglyphus balkei Hendrich (Coleoptera: Dytiscidae: Bidessini) with phylogenetic considerations - Michat, Mariano C.; Alarie, Yves; Watts, Chris H. S. (Zootaxa, 2010)
The first-instar larva of Neobidessodes Hendrich & Balke (through the hypogaeic species N. limestoneensis (Watts & Humphreys)) and the third-instar larva of Hydroglyphus Motschulsky (through H. balkei Hendrich) (Dytiscidae: Bidessini) are described and illustrated in detail for the first time, including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. A cladistic analysis including 51 characters and 32 hydroporine taxa is performed, which supports the inclusion of both genera in the tribe Bidessini based on the absence of the primary pore ABc on the last abdominal segment. The third instar of H. balkei is characterized by the absence of secondary setae on the urogomphi and anterior secondary setae on the coxa, and the presence of 8–9 secondary setae on the mesofemur. On the other hand, the first instar of N. limestoneensis bears 14 lamellae clypeales on the anteroventral margin of the nasale. This species has evolved several morphological characters that are probably associated with its hypogaeic existence, including a lightly sclerotized body, relatively longer cephalic capsule and mandibles, a strongly reduced occipital foramen, absence of stemmata, and short claws. However, primary chaetotaxy apparently has remained as a very conservative expression of the phenotype.